Eksplorasi Peran Bidan dan Dukungan Keluarga Dalam Mempromosikan Pemberian ASI Eksklusif di Puskesmas Indraloka Jaya Tahun 2025 - Marsya Soleha; Novita Novita (Jurnal Ners, 2025)
The reality that occurs in society is that breastfeeding is only a matter between the mother and baby, even though in reality there are many factors that influence the success of exclusive breastfeeding. One of the important factors that supports the success of exclusive breastfeeding is providing support to mothers both from the family and from health workers, especially midwives. Based on the background description above, the author is interested in conducting research with the title "Exploring the Role of Midwives and Family Support in Promoting Exclusive Breastfeeding at the Indraloka Jaya Health Center in 2025". To find out the relationship between midwife support and family support for exclusive breastfeeding in the working area of ​​the Indraloka Jaya Health Center.This research is an analytical survey research with a cross sectional approach. The research population was 45 mothers who had babies aged 6 - 11 months and the total sample was 45 people with sampling using purposive sampling. Data analysis in this study was univariate analysis, bivariate analysis with chi square, and multivariate analysis with multiple logistic regression using statistical calculations from the SPSS program.The results of data analysis obtained a p value of midwife support (0.001) and family support (0.000) for exclusive breastfeeding, meaning that there is a significant relationship between midwife support and family support for exclusive breastfeeding. Based on multiple logistic regression analysis, it was found that midwife support provides 5,135 times the opportunity and family support provides 23,981 times the opportunity for exclusive breastfeeding.Based on the research results, there is a relationship between midwife support and family support for exclusive breastfeeding in the Indraloka Jaya Health Center working area. Midwives or other health workers should provide education to family members so they can provide support to the mother during breastfeeding